1990
DOI: 10.1007/bf02381029
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the behaviour of immature captive lowland gorillas

Abstract: ABSTRACT. Studies of the behaviour of 26 (12 males and 14 females) captive infant and juvenile lowland gorillas showed clear sex differences. Females showed greater interest in young infants and were more active in nest building as well as in solitary and social grooming. Males were more active in locomotive, dominance, and aggressive behaviour and in social play. Hand-rearing further increased aggression. Males were more aggressive when they lived with only one partner, and they rose in rank even above older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Sex differences were also found: female infants engaged in significantly higher levels of self-directed behavior than males. Meder [1990] found that among the 26 animals she studied in Europe, female infant gorillas engaged in significantly more autogrooming (a component of self-directed behavior). This may reflect the tendency for female infant gorillas to engage in more nonsocial than social activities compared to male infants [Aspinall, 1983;Meder, 19901.…”
Section: Discussionmentioning
confidence: 95%
“…Sex differences were also found: female infants engaged in significantly higher levels of self-directed behavior than males. Meder [1990] found that among the 26 animals she studied in Europe, female infant gorillas engaged in significantly more autogrooming (a component of self-directed behavior). This may reflect the tendency for female infant gorillas to engage in more nonsocial than social activities compared to male infants [Aspinall, 1983;Meder, 19901.…”
Section: Discussionmentioning
confidence: 95%
“…). Moreover, proximity is less likely to be strongly influenced by developmental stage or sex than other behavioral measures, such as play and grooming which change in frequency with age (Meder ; Maestripieri & Ross ; Rosenbaum et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Avoidance of close proximity may be used to deter aggression, particularly for male gorillas (e.g., Robbins 1996), and initiating or maintaining close proximity is a primary reconcilia-tion mechanism in western lowland gorillas (Mallavarapu et al 2006). Moreover, proximity is less likely to be strongly influenced by developmental stage or sex than other behavioral measures, such as play and grooming which change in frequency with age (Meder 1990;Maestripieri & Ross 2004;Rosenbaum et al 2011). This is important because we are interested in evaluating the changes in social relationships across developmental stages.…”
Section: Measuring Social Relationshipsmentioning
confidence: 99%
“…Although the influence of these factors has yet to be examined adequately in a welfare context, the existing literature indicates that all are related to individual differences in behavior for a number of primate species, including gorillas. For example, immature female gorillas show more interest in young infants and spend more time in nest building and grooming, whereas males spend more time engaged in aggressive behaviors and social play [Maestripieri and Ross, ; Meder, ]. Rearing history, and in particular mother vs. hand rearing, has been linked to numerous behavioral differences in immature and adult gorillas of both sexes [Gold, ; Meder, ; Ryan et al, ; Stoinski et al, , ].…”
Section: Introductionmentioning
confidence: 99%